2021
DOI: 10.29333/iji.2021.14219a
|View full text |Cite
|
Sign up to set email alerts
|

Reflective Teaching Perceived and Practiced by EFL Teachers - A Case in the South of Vietnam

Abstract: Reflective teaching (RT) is one of the core components of teacher professional development. Owing to its substantive importance in teacher education, this component has been long recognized and widely examined in various approaches. However, it is not the case in Vietnam. Thus, the present study was done to investigate how RT was perceived and practiced by a local group of in-service EFL teachers in an English language center located in Can Tho City, South of Vietnam. Data were collected via a questionnaire, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…A closer analysis regarding the sub-components of reflective practice indicated that the participant Turkish EFL teachers further favor keeping a file for revision (the practical component), reading publications related to effective teaching to improve their inclass performance(the cognitive component), getting feedback from the students (the affective/learner component), thinking about their strengths and weaknesses as teachers of English (the metacognitive component) and similarly, thinking of ways promoting tolerance and democracy in their classes and in the society in general (the critical component). On the other hand, it is apparent that most of the participants scarcely think of writing articles based on their classroom experiences, which requires indeed a training on academic research and article writing, and asking their colleagues to observe their teaching and their comment on their own teaching performance, akin to the recent findings obtained by Hung and Thuy (2021). By the same token, they relatively less think about the political aspects of their teaching and its influence on their students' political views, which is unlike the results indicating rather more interest in socio-political aspects of teaching by Moghaddam et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…A closer analysis regarding the sub-components of reflective practice indicated that the participant Turkish EFL teachers further favor keeping a file for revision (the practical component), reading publications related to effective teaching to improve their inclass performance(the cognitive component), getting feedback from the students (the affective/learner component), thinking about their strengths and weaknesses as teachers of English (the metacognitive component) and similarly, thinking of ways promoting tolerance and democracy in their classes and in the society in general (the critical component). On the other hand, it is apparent that most of the participants scarcely think of writing articles based on their classroom experiences, which requires indeed a training on academic research and article writing, and asking their colleagues to observe their teaching and their comment on their own teaching performance, akin to the recent findings obtained by Hung and Thuy (2021). By the same token, they relatively less think about the political aspects of their teaching and its influence on their students' political views, which is unlike the results indicating rather more interest in socio-political aspects of teaching by Moghaddam et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, associations have been found between reflective teaching practices and teacher empowerment (Oo et al, 2023) as well as professional growth (Mermelstein, 2018). Through critical analysis of their own practices, teachers can acquire a more precise understanding of their strengths and areas needing enhancement, thus spurring personal and professional development (Hung & Thuy, 2021).…”
Section: Implications Of Reflective Teaching Practicesmentioning
confidence: 99%
“…Additionally, pre-service instructors could reconstruct their professional identities in their network of effective teaching due to reflective journals for critical reflection. Their individuality, consciousness, expertise, and assurance in instructing were all developed, which improved productivity levels (Hung et al, 2021). For instance, a poll of eight pre-service instructors in research by Dumlao & Pinatacan (2019) indicated that they grappled with how to educate their pupils because their instructional expertise in an EFL setting forced them to modify and evolve their instructional techniques.…”
Section: Literature Reviewmentioning
confidence: 99%